HBR's 10 Must Reads on Platforms and Ecosystems (with bonus article by ""Why Some Platforms Thrive and Others Don't"" By Feng Zhu and Marco Iansiti) - Iansiti, Marco, 1961-; Lakhani, Karim R.; Van Alstyne, Marshall; Parker, Geoffrey (Geoffrey G.); Harvard Business Review Press (La Vergne : Harvard Business Review Press, 2020)
Help your company adapt to the new rules of competition. If you read nothing else on creating value with business platforms and ecosystems, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you reap the rewards of multisided platforms (MSPs),or defend your company against these formidable opponents. This book will inspire you to: -Assess the threat of disruption from platforms in your industry -Decide whether and how to play with increasingly powerful platform businesses -Choose the right strategy for transforming your product into a platform -Harness network effects to maximize value for the partners in your ecosystem -Shift from managing products to managing interactions -Learn when moving first and growing fast will work,and when it won't -Manage winner-take-all dynamics This collection of articles includes "Pipelines, Platforms, and the New Rules of Strategy," by Marshall W. Van Alstyne, Geoffrey G. Parker, and Sangeet Paul Choudary; "Strategies for Two-Sided Markets," Thomas R. Eisenmann, Geoffrey Parker, and Marshall W. Van Alstyne; "Finding the Platform in Your Product," by Andrei Hagiu and Elizabeth Altman; "What's Your Google Strategy'," by Andrei Hagiu and David B. Yoffie; "In the Ecosystem Economy, What's Your Strategy'," by Michael G. Jacobides; "Right Tech, Wrong Time," by Ron Adner and Rahul Kapoor; "Managing Our Hub Economy," by Marco Iansiti and Karim R. Lakhani; "Why Some Platforms Thrive and Others Don't," by Feng Zhu and Marco Iansiti; "Spontaneous Deregulation," by Benjamin Edelman and Damien Geradin; "Alibaba and the Future of Business," by Ming Zeng; and "Fixing Discrimination in Online Marketplaces," by Ray Fisman and Michael Luca. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their c
Intro -- Contents -- Ch. 1: Pipelines, Platforms, and the New Rules of Strategy -- Ch. 2: Strategies for Two-Sided Markets -- Ch. 3: Finding the Platform in Your Product -- Ch. 4: What's Your Google Strategy? -- Ch. 5: In the Ecosystem Economy, What's Your Strategy? -- Ch. 6: Right Tech, Wrong Time -- Ch. 7: Managing Our Hub Economy -- Ch. 8: Why Some Platforms Thrive . . . and Others Don't -- Ch. 9: Spontaneous Deregulation -- Ch. 10: Alibaba and the Future of Business -- Ch. 11: Fixing Discrimination in Online Marketplaces -- About the Contributors -- Index
Description based upon print version of record.
Added to collection customer.56279.3
Keywords: Competition; Business planning; BUSINESS & ECONOMICS / Free Enterprise & Capitalism; elektronické knihy; electronic books